‘It's just drama’: teen perspectives on conflict and aggression in a networked era - Marwick, Alice; boyd, danah (Journal of Youth Studies, 2014)
Contemporary youth conflict often plays out through social media like Facebook and Twitter. ‘Drama’ is an emergent concept describing performative, interpersonal conflict that takes place in front of an active, engaged audience, often on social media. Using ethnographic data, this paper examines how American teenagers conceptualize the term drama; the relationship between drama and social media; and the implications drama has for understanding contemporary teenage conflict. The emic use of drama distances teens from practices conceptualized by adults as bullying or relational aggression, while acknowledging the role of the audience in social media interactions. Drama also serves to reinforce the conventional gendered norms of high school, perpetrating the systemic undervaluing of feminine subjects and re-inscribing heteronormativity. Understanding how drama operates helps illuminate how widespread use of social media among teenagers has altered dynamics of aggression and conflict.